Oral Administration of Lactiplantibacillus plantarum KBL396 Regulates Serum 5-Hydroxytryptamine and Gut Microbiota: Evidence from a Preclinical Mouse Model and a Randomized Controlled Human Trial - Woojae Myung; Sung Jae Jang; Giljae Lee; Cheonghoon Lee; Kiuk Lee; Sung Hyun Moon; Yunsun Jeong; Woon-Ki Kim; SungJun Park; Hyungjin Lee; Yun Seong Park; Sangah Shin; et al. (Probiotics and Antimicrobial Proteins, 2026)

Limosilactobacillus fermentum KBL674 Alleviates Vaginal Candidiasis - Sung Jae Jang; Eun Jung Jo; Cheonghoon Lee; Bo-Ram Cho; Yun Jeong Shin; Jun Soo Song; Woon-Ki Kim; Nanhee Lee; Hyungjin Lee; SungJun Park; GwangPyo Ko (Probiotics and Antimicrobial Proteins, 2025)
Candida albicans ( C. albicans ) is the primary etiologic agent of vaginal candidiasis. Lactobacillus species are predominant in the vaginal microbiome; they inhibit the development of vaginal candidiasis by producing antimicrobial agents, such as lactic acid and hydrogen peroxide. In this study, we investigated the effects of Limosilactobacillus fermentum ( L. fermentum ) KBL674 in a mouse model of vaginal candidiasis. L. fermentum KBL674 inhibited C. albicans hyphal growth. Moreover, oral administration of L. fermentum KBL674 significantly suppressed vaginal C. albicans infection and associated symptoms, including tissue thickness and immune cell infiltration. A substantial quantity of L. fermentum KBL674 was excreted by the mice within 6 h after oral administration, indicating that most L. fermentum KBL674 did not settle within the gastrointestinal tract. L. fermentum KBL674 modulated gut microbiome diversity, increasing abundances of the genera Akkermansia , Eubacterium , and Faecalibaculum and family Muribaculaceae . Abundances of these bacteria showed negative correlations with the vaginal C. albicans burden in the mouse model, suggesting links between the gut microbiome composition and the vaginal C. albicans burden . Therefore, L. fermentum KBL674 can reduce the vaginal C. albicans burden via direct or indirect inhibition and modulation of the gut microbiome composition preventively. Graphical Abstract

Oral Administration of Limosilactobacillus reuteri KBL346 Ameliorates Influenza Virus A/PR8 Infection in Mouse - Doseon Choi; Sung Jae Jang; Sueun Choi; SungJun Park; Woon-Ki Kim; Giljae Lee; Cheonghoon Lee; GwangPyo Ko (Probiotics and Antimicrobial Proteins, 2025)
Influenza virus infection is an important public-health concern because of its high transmissibility and potential for severe complications. To mitigate the severity and complications of influenza, probiotics containing Lactobacillus are used and generally recognized as safe. We evaluated the anti-influenza effect of Limosilactobacillus reuteri ( L. reuteri ) KBL346, isolated from the fecel sample of healthy South Koreans, in mice. BALB/c mice were orally administered live and heat-inactivated L. reuteri KBL346. After infection with influenza virus (A/Puerto Rico/8/34) 0.5 times the 50% lethal dose (LD 50 ), body weight loss was improved and recovery was accelerated. Furthermore, L. reuteri KBL346 improved body weight loss and survival rate of mice infected with 4 times the LD 50 of influenza virus. Heat-inactivated L. reuteri KBL346 reduced the viral titer in the lung and the plasma immunoglobulin G level. Expression levels of genes encoding inflammatory cytokines, such as interferon-γ and toll-like receptor 2 ( Tlr2 ), were decreased in the lung tissues of mice administered L. reuteri KBL346. Live and heat-inactivated L. reuteri KBL346 increased the expression level of Adamts4 , which promotes recovery after infection, and decreased that of Tlr2 . The α-diversity of the gut microbiome was modulated by the administration of L. reuteri KBL346. In addition, the structure of the gut microbial community differed according to the degree of weight loss. L. reuteri KBL346 has the potential to alleviate disease severity and improve histopathological changes in mice infected with influenza A/PR8, suggesting its efficacy as a probiotic against influenza infection.

Assessment of the filtration efficiency and antibacterial activity of reusable antibacterial face masks after washing - Yeram Yang; Jongmin Park; Sueun Choi; Kiyoung Lee; Cheonghoon Lee; Chungsik Yoon (Air Quality, Atmosphere & Health, 2025)
This study evaluated the filtration efficiency, and continuity of the antibacterial activity of reusable antibacterial silver, copper, and graphene antibacterial masks before and after washing. The masks were washed at three different temperatures (40 °C, 60 °C, 90 °C) and up to 10 washing cycles. The filtration efficiencies of the three reusable antibacterial masks were between 10 and 13% before washing and increased by approximately 6% after washing. Before washing, the bacterial filtration efficiency was between 93 and 98%. The antibacterial activity was 98% for both the silver and copper masks, and 88% for the graphene mask. All these values were higher than those of non-antibacterial masks. There were no trends in performance difference with increasing washing temperature or cycles, and performance did not change significantly compared to before washing, regardless of the temperature or washing cycles. Under certain testing conditions, the bacterial filtration efficiency of the three reusable antibacterial masks was Graphical Abstract

Male-Specific and Somatic Coliphage Profiles from Major Aquaculture Areas in Republic of Korea - JaeYoon Lee; SungJun Park; Cheonghoon Lee; Kyuseon Cho; Yong Seok Jeong; Young-Mog Kim; Kwon-Sam Park; Jong Duck Choi; Yongsik Sin; GwangPyo Ko (Food and Environmental Virology, 2020)

Isolation and characterization of a novel Escherichia coli O157:H7-specific phage as a biocontrol agent - Cheonghoon Lee; In Young Choi; Do Hyeon Park; Mi-Kyung Park (Journal of Environmental Health Science and Engineering, 2020)

Comparison of Swab Sampling Methods for Norovirus Recovery on Surfaces - Cheonghoon Lee; SungJun Park; Kyuseon Cho; Ju Eun Yoo; Sunghee Lee; GwangPyo Ko (Food and Environmental Virology, 2018)

Use of coliphages to investigate norovirus contamination in a shellfish growing area in Republic of Korea - Kyuseon Cho; Cheonghoon Lee; SungJun Park; Jin Hwi Kim; Yong Seon Choi; Man Su Kim; Eung Seo Koo; Hyun Jin Yoon; Joo-Hyon Kang; Yong Seok Jeong; Jong Duck Choi; GwangPyo Ko (Environmental Science and Pollution Research, 2018)

Inactivation of influenza A virus via exposure to silver nanoparticle-decorated silica hybrid composites - SungJun Park; Young-Seon Ko; Su Jin Lee; Cheonghoon Lee; Kyoungja Woo; GwangPyo Ko (Environmental Science and Pollution Research, 2018)